Comparison of The Efficacy of Oral Versus Topical NSAIDs for Pain Relief in Osteoarthritis: Comparison of The Efficacy of Oral Versus Topical NSAIDs - Zeb, Alam; Din, Imad Ud; Ali, Amjad; Najeebullah, .; Ahmad, Hajra; Ali, Usman (Pakistan Journal of Health Sciences, 2025)
Osteoarthritis is a leading cause of chronic musculoskeletal pain worldwide, significantly impairing quality of life and increasing healthcare burden. Nonsteroidal anti-inflammatory drugs (NSAIDs), administered orally or topically, remain the mainstay of symptom management, though their relative efficacy and safety profiles require further evaluation. Objectives: To compare the efficacy of oral versus topical NSAIDs for pain relief in osteoarthritis. Methods: This quasi-experimental study was conducted at the Department of Rheumatology, Khyber Teaching Hospital, Peshawar, during the period February 2025 to May 2025. 132 male and female patients aged more than 50 years diagnosed with osteoarthritis were assigned to topical (n=66) and oral NSAID (n=66) groups. Diclofenac gel and tablet diclofenac 50mg BD were administered for 4 weeks, respectively. Patients were evaluated for pain relief using the VAS score. Results: Mean age in topical versus oral NSAIDs was 64.73±8.25 years versus 66.55±9.606 years, respectively. Male participants were 41 (52.6%) and 37(47.4%) in topical and oral groups, respectively. 23(50.0%) had bilateral joint involvement in both groups. Pain relief was recorded in 25 patients (37.9%) with topical NSAIDs compared to 35 (53.1%) with oral NSAIDs (p-value 0.080). Conclusions: Statistically insignificant difference in pain relief was recorded with topical and oral NSAIDs in patients with chronic MSK pain of osteoarthritis. Though the proportion of pain relief was better with oral NSAIDs, the difference was statistically not significant.